Evaluasi Gangguan Otot Rangka pada Pekerjaan Manual Material Handling dengan Pendekatan Composite Lifting Index - Annaufal, Sultan Syafiq; Amrullah, Haidar Natsir; Santoso, Mochamad Yusuf (Journal of Safety, Health, and Environmental Engineering, 2025)
Occupational diseases are health problems that can be caused by work and the work environment. One such work activity that can lead to occupational diseases is the manual loading of bags and palletizing, which is a process known as Manual Material Handling. This process involves lifting, lowering, pushing, pulling, and carrying objects by hand. A survey using SNI 9011: 2021 on bag loading and palletizing work revealed a high risk of musculoskeletal disorders at 41%, a moderate risk at 33%, and a low risk at 26%. To address these musculoskeletal complaints, an analysis of Manual Material Handling using the Composite Lifting Index was conducted, as this work involves multiple tasks. The Composite Lifting Index analysis yielded a value of ∞, indicating the work is hazardous. In response to the Manual Material Handling assessment, recommendations, such as modifying the conveyor to align with the anthropometry of Indonesian men, hydraulic adjustment of pallets, and posture improvement during palletizing, are suggested